Reform in the making : the implementation of social policy in prison - Lin, Ann Chih (Princeton University Press, 2000)
Is it time to give up on rehabilitating criminals? Record numbers of Americans are going to prison, and most of them will eventually return to society with a high chance of becoming repeat offenders. But a decision to abandon rehabilitation programs now would be premature warns Ann Chih Lin, who finds that little attention has been given to how these programs are actually implemented and why they tend to fail. In Reform in the Making, she not only supplies much-needed information on the process of program implementation but she also considers its social context, the daily realities faced by.